Replacement of TCR Dβ With Immunoglobulin DH DSP2.3 Imposes a Tyrosine-Enriched TCR Repertoire and Adversely Affects T Cell Development - Levinson, Michael; Khass, Mohamed; Burrows, Peter D.; Schroeder, Harry W. (Frontiers in Immunology, 2020)
Enrichment for tyrosine in immunoglobulin CDR-H3 is due in large part to natural selection of germline immunoglobulin DH sequence. We have previously shown that when DH sequence is modified to reduce the contribution of tyrosine codons, epitope recognition is altered and B cell development, antibody production, autoantibody production, and morbidity and mortality following pathogen challenge are adversely affected. TCRB diversity (DB) gene segment sequences are even more highly conserved than DH, with trout DB1 identical to human and mouse DB1. We hypothesized that natural selection of DB sequence also shapes CDR-B3 diversity and influences T cell development and T cell function. To test this, we used a mouse strain that lacked DB2 and contained a novel DB1 allele (DBYTL) that replaces DB1 with an immunoglobulin DH, DSP2.3. Unlike DB1 wherein glycine predominates in all three reading frames (RFs), in DSP2.3 there is enrichment for tyrosine in RF1, threonine in RF2, and leucine in RF3. Mature T cells using DBYTL expressed TCRs enriched at particular CDR-B3 positions for tyrosine but depleted of leucine. Changing DB sequence altered thymocyte and peripheral T cell numbers and the T cell response to an ovalbumin immunodominant epitope. In general, TCR are considered to be more polyspecific with lower affinity for their cognate antigens than their immunoglobulin counterpart. It is possible that enrichment for tyrosine in CDR-H3 could help explain why chimeric antigen receptor (CAR) T cells benefit from the use of immunoglobulin V domains.